Electrical safety: safety and health for electrical trades - USA. National Institute for Occupational Safety and Health (Cincinnati, 2002)
"This student manual is part of a safety and health curriculum for secondary and post-secondary electrical trades courses. The manual is designed to engage the learner in recognizing, evaluating, and controlling hazards associated with electrical work. It was developed through extensive research with vocational instructors, and we are grateful for their valuable contributions."